Human Motion Understanding, Modelling, Capture, and Animation - Rosenhahn, Bodo.; Klette, Reinhard; Metaxas, Dimitris; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The study of human motion dates back more than 2000 years. With the event of information technology, new areas have been added to this field. Research using computer vision and computer graphics contributes to a transformation of biomechanics into a discipline that now applies computing technology throughout; on the other hand, computer vision and computer graphics also benefit from defining goals aimed at solving problems in biomechanics. Besides interactions, all three areas also developed their own inherent research dynamics towards studying human motion. Researchers from all three of these areas have contributed to this book to promote the establishment of human motion research as a multi-facetted discipline and to improve the exchange of ideas and concepts between these three areas. Some chapters review the state of the art whilst others report on leading edge research results, with applications in medicine, sport science, cinematography and robotics.
2D Tracking -- Understanding Human Motion: A Historic Review -- The Role of Manifold Learning in Human Motion Analysis -- Recognition of Action as a Bayesian Parameter Estimation Problem over Time -- The William Harvey Code: Mathematical Analysis of Optical Flow Computation for Cardiac Motion -- Detection and Tracking of Humans in Single View Sequences Using 2D Articulated Model -- Learning -- Combining Discrete and Continuous 3D Trackers -- Graphical Models for Human Motion Modelling -- 3D Human Motion Analysis in Monocular Video: Techniques and Challenges -- Spatially and Temporally Segmenting Movement to Recognize Actions -- Topologically Constrained Isometric Embedding -- 2D-3D Tracking -- Contours, Optic Flow, and Prior Knowledge: Cues for Capturing 3D Human Motion in Videos -- Tracking Clothed People -- An Introduction to Interacting Simulated Annealing -- Motion Capture for Interaction Environments -- Markerless Motion Capture for Biomechanical Applications -- Biomechanics and Applications -- Qualitative and Quantitative Aspects of Movement: The Discrepancy Between Clinical Gait Analysis and Activities of Daily Life -- Optimization of Human Motion Exemplified with Handbiking by Means of Motion Analysis and Musculoskeletal Models -- Imitation Learning and Transferring of Human Movement and Hand Grasping to Adapt to Environment Changes -- Accurate and Model-free Pose Estimation of Crash Test Dummies -- Modelling and Animation -- A Relational Approach to Content-based Analysis of Motion Capture Data -- The Representation of Rigid Body Motions in the Conformal Model of Geometric Algebra -- Video-based Capturing and Rendering of People -- Interacting Deformable Objects -- From Performance Theory to Character Animation Tools.
Keywords: COMPUTER SCIENCE; HUMAN PHYSIOLOGY; SPORTS MEDICINE; COMPUTER VISION; COMPUTER SCIENCE; COMPUTER IMAGING, VISION, PATTERN RECOGNITION AND GRAPHICS; IMAGE PROCESSING AND COMPUTER VISION; HUMAN PHYSIOLOGY; SPORTS MEDICINE